Gen Z as Digital Catalysts in Transforming Mosque Communication Service - Nur Setiawati; Ikhwan As-ad; Ali Halidin; Abdul Wahid (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2025)
In the context of rapid digital transformation and shifting patterns of religious engagement among younger generations, effective communication has become a critical challenge for mosque institutions in urban Muslim societies. This study examines the communication gap between mosque administrators and Generation Z in Makassar, exploring the potential of Gen Z as digital catalysts in transforming mosque communication for inclusive community service. The research employs a mixed-methods approach. Quantitative data were collected through questionnaires from 300 Gen Z individuals, while qualitative data were gathered through in-depth interviews with key stakeholders, including mosque administrators, religious leaders, community leaders, and youth figures, to explore their perspectives and communication challenges. The findings reveal that Gen Z heavily relies on visual and interactive digital platforms (Instagram, TikTok, WhatsApp) and feels that current mosque communication is unengaging and irrelevant. There is broad acknowledgment of this communication gap from all stakeholders. Key findings indicate Gen Z's willingness to get involved and use their digital skills to manage mosque social media, with a strong desire for creative freedom.